DETERMINANTS OF RESPONSES TO ANTIMALARIAL DRUGS IN CHILDREN WITH UNCOMPLICATED PLASMODIUM FALCIPARUM MALARIA (2011)
Drug resistance is a challenge to malaria control efforts and several factors including parasite genetics, host factors and pharmacokinetics may contribute to the selection of drug resistant Plasmodium falciparum. Understanding the role of these factors in patient response to antimalarial drugs is therefore essential in the management of malaria. The aim of the study was to determine the factors contributing to delay in malaria Parasite Clearance (PC) in children and evaluating the effects of pharmacokinetic variability on treatment outcome. Children (n=2,752), aged 6 months -12 years, with falciparum malaria, were enrolled over a period of eight years and treated with standard doses of Chloroquine (CQ), Sulphadoxine-Pyrimethamine (SP) or Amodiaquine (AQ) given alone or in combination with artemisinin. Each patient was followed up for at least 14 days. Age, axillary temperature, parasite density and gametocytaemia were assessed for their potential association with delay in PC and treatment outcomes. Filter-paper blood samples were collected from some of the children (n=148) before treatment and on days 1-7, 14, 28 and 35 after treatment for determination of CQ and sulphadoxine concentrations. In another subset of patients (n=7), treated with amodiaquine, blood and saliva samples were collected over 35 days. High performance liquid chromatographic techniques were used to determine concentrations of sulphadoxine in whole blood as well as AQ and Desethyl amodiaquine (DEAQ) in saliva. Mean maximum drug concentration (Cmax), half-life (t1/2) and area under concentration-time curve (AUC0-28d) were assessed for their association and predictive value for treatment outcomes. Data were analyzed using descriptive statistics, ANOVA, Chi-square, Students’ t-test, Kruskal-Wallis and multiple regressions at p = 0.05. Age ≤ 2 years (Adjusted odds ratio [AOR] = 2.13), presence of fever (AOR = 1.33) and parasitaemia > 50,000/µl (AOR = 2.21) at enrolment were independent risk 3 factors for delay in PC, while a body temperature >38OC and parasitaemia >20,000/µl were predictors a day after treatment regardless of the drug used. Day 3 concentration ≤ 1750ng/ml and AUC0-28d ≤ 950ng/ml.h were associated with chloroquine treatment failure. In a multivariate analysis, a terminal elimination t½ ≤ 220h (AOR = 0.28) and AUC0-28d ≤ 950ng/ml.h (AOR = 4.12) were identified as independent pharmacokinetic predictors of chloroquine treatment failure. Age stratified analysis showed that SDX concentrations were significantly higher in children > 5years compared to children <5years: Cmax; 295 vs 125µg/ml, AUC0-28d; 1562 vs 812µg/ml.d. In patients who received AQ, there was a rapid conversion of AQ to DEAQ, which was detectable in plasma and saliva within 40 minutes of administration. The mean day 7 concentration of DEAQ was significantly higher in plasma than in saliva (247.8 vs 125.1ng/ml). The t1/2 of DEAQ were similar in plasma (167.25±43.4h) and saliva (146.12±17.2h). The decline phases of DEAQ in saliva concentration-time curves were approximately similar to that in plasma. Delay in parasite clearance is specific and related to drug resistance. In addition pharmacokinetic variability of sulphadoxine in children has potential impact on dosage regimen and treatment outcome.